Pelatihan Keamanan Data Pada Penggunaan Microsoft Office Bagi Guru di SDIT Mutiara Bekasi - Nurfiyah, Nurfiyah; Salkiawati, Ratna; Lubis, Hendarman (Journal Of Computer Science Contributions (JUCOSCO), 2023)
Information Technology Security is increasingly advanced, not only in the world of the manufacturing industrybut also penetrates the world of education. This forces educators to be able to develop their abilities to know howto secure data in Ms.Office. Therefore, as a manifestation of Bhayangkara Jakarta Raya University's commitmentto carrying out the Tri Dharma of Higher Education in community service, the Informatics Study Program carriedout activities with the theme "Data Security Training on the Use of Ms.Office at SDIT Mutiara" as an effort toapply knowledge about information technology security. At the moment. The purpose of this training is to increaseknowledge and insight for participants in terms of Data Security at Ms. Office, as well as providing training tomake data security and broaden knowledge of the use of Ms. Office for teachers of SDIT Mutiara. The materialprovided in this training is in the form of an introduction to the concept of Data Security, types of software inmaking teaching materials with Ms. office. The methodology for carrying out this activity begins with datacollection, determining the theme of the service to be given, literature study, making training materials, presentingtraining. The result of this training is an increased understanding of data security by 97%. From the data securitytraining activities in Microsoft Office that have been carried out for teachers and administrators of SDIT MutiaraBekasi, it can be seen that the participants were very enthusiastic and motivated to do security for their data sothat during the training the participants did not feel bored with the material delivered by the tutor.